International Economics : Theory and Policy, Global Edition. - Krugman, Paul.; Obstfeld, Maurice; Melitz, Marc.; ProQuest (firma) (Harlow : Pearson Education, Limited, 2022)
Engage your students in the key concepts of international theory and policy. International Economics: Theory and Policy, 12th Edition provides a balanced coverage of global theory and policy. With an array of features and examples, this edition will equip your students with the skills to understand the developments in the changing global economy.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books